A48 USE OF ENDOSCOPIC ULTRASOUND FINE NEEDLE ASPIRATE AND ENDOSCOPIC ULTRASOUND FINE NEEDLE BIOPSY FOR DETECTION OF GATA6 EXPRESSON IN PANCREATIC DUCTAL ADENOCARINCOMA. (4th March 2021) - Law, C; Fischer, S; Knox, J; Gallinger, S; Ramotar, S; Anna, D; May, G; James, P D
Abstract: Background: GATA6 is a transcription factor that can be used to distinguish between the basal-like and classical subtypes of pancreatic ductal adenocarcinoma (PDAC). The basal-like subtype has been demonstrated to be less responsive to modified FOLFIRINOX chemotherapy and thus can be used to predict response to specific chemotherapies. To date, GATA6 expression has only been evaluated in surgically resected PDAC specimens. Less than 15% of patients with PDAC are eligible for surgery. Endoscopic ultrasound guided fine-needle aspirate (EUS-FNA) and biopsy (EUS-FNB) can potentially help assess GATA6 expression in PDAC and in turn, help guide personalized treatment selection in all cases of PDAC. Aims: The primary objective of this study was to explore the yield of EUS-FNA and EUS-FNB for the detection of GATA6 among patients with PDAC. The study also aimed to explore the impact of lesion location on sample adequacy and type of fixative on validity of GATA6 staining. Methods: This study was conducted from November 2017 to October 2019. Consecutive patients with a diagnosis of PDAC confirmed by biopsy were included. Patients underwent either EUS-FNB or EUS-FNA to obtain tissues samples. Samples were fixed in either neutral buffered formalin (NBF) or a methanol based buffered solution (Cytolyt) and evaluated by a specialized cytopathology team. Fisher's exact test was used and a p-value ≤0.05 was considered to indicate statistical significance. Results: Forty-four patients were included in the study. Twenty-three (52%) patients were male and the median age of patients was 67.5 years. Twenty-five lesions were located in the head and neck of the pancreas, 14 were located in the body, and 4 were located in the tail. One patient was found to have a local recurrence of PDAC at the surgical bed of a previous Whipple procedure. Eighteen lesions were sampled by EUS-FNA and 26 were sampled using EUS-FNB. Thirty-eight (86%) samples were adequate for assessment of GATA6. Sampling technique (p=0.68) and fixative type (p=1.00) did not appear to affect sample adequacy. Compared to pancreatic body or tail specimens, samples obtained from the head or neck of the pancreas were more likely to be inadequate for analysis (p=0.03). Conclusions: EUS-FNA and EUS-FNB samples are efficacious methods of assessing GATA6 expression in PDAC. This is the first predictor of treatment response that has been demonstrated to be obtained without surgical resection. Neither EUS needle type or alcohol fixation before cell block preparation appear to impact GATA6 detection. Lesions in the pancreatic head or neck appear to be associated with higher rates of sample inadequacy. Larger, prospective studies are required to confirm our findings. Funding Agencies: None